VENDIAN ROCKS OF THE WESTERN PART OF THE EAST EUROPEAN PLATFORM: STRATOTYPIC RANGE, BOUNDARIES AND PRINCIPLES OF THEIR ESTABLISHMENT - Makhnach A.S.; Veretennikov N.V.; Shkuratov V.I. (My University, 1986)
The Vendian in a stratotype area in the western part of the East European Platform includes three regional stratigraphic subdivisions: the Vilchanian, Volynian and Valdaian series, which clearly differ in structure and lithology. They are closely interconnected stratigraphically and geochronologically, and form an indivisible Late Baikalian structural stage of the platform sedimentary cover. The upper subdivision, the Valdaian Series, is palaeontologically substantiated and divided into horizons. The Vendian in such a composition has definite boundaries: the upper biostratigraphic, and lower lithostratigraphic ones, and is well correlated with the formations of the same age from other regions.
Keywords: Vendian; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский